Exploring the Insurance-Growth Nexus: Life vs. Non-Life Insurance in Saudi Arabia - Alsuhaibani, Emtinan; Drissi, Ramzi; Zahran, Mohamed (Contemporary Mathematics, 2025)
This paper explores the relationship between insurance and economic growth in Saudi Arabia from 1992 to 2022, focusing on the distinct impacts of life and non-life insurance sectors. Using a nonlinear autoregressive distributed lag (NARDL) model, the research analyzes the insurance-growth nexus while capturing asymmetries in both short and long-term relationships. The analysis shows a significant positive correlation between life insurance penetration and GDP per capita growth, whereas no substantial link is observed for non-life insurance penetration. These results underscore the potential of life insurance in diversifying income sources and reducing oil dependency within the Saudi economy. The research indicates that increased life insurance penetration could create a multiplier effect, fostering financial stability, encouraging savings, and stimulating economic growth. This effect may also extend to other regions with similar economic structures. The findings have important implications for policymakers and stakeholders in the insurance industry, particularly in economies seeking to reduce their reliance on natural resources and diversify their economic base by highlighting the role of the life insurance sector in economic development.